2023
DOI: 10.1101/2023.01.24.23284916
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-world effectiveness of molnupiravir, nirmatrelvir-ritonavir, and sotrovimab on preventing hospital admission among higher-risk patients with COVID-19 in Wales: a retrospective cohort study

Abstract: Objective To compare the effectiveness of molnupiravir, nirmatrelvir-ritonavir, and sotrovimab with no treatment in preventing hospital admission or death in higher-risk patients infected with SARS-CoV-2 in the community. Design Retrospective cohort study of non-hospitalised adult patients with COVID-19 using the Secure Anonymised Information Linkage (SAIL) Databank. Setting A real-world cohort study was conducted within the SAIL Databank (a secure trusted research environment containing anonymised, individual… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 23 publications
(36 reference statements)
2
19
0
Order By: Relevance
“…Real world effectiveness studies from Israel, Hong Kong, and the UK provided evidence of the effectiveness of nirmatrelvir during the early days of the omicron surge when BA.1 or BA.2 was the predominant subvariant. [3][4][5] Most people infected in the omicron predominant era had been vaccinated (80% of people in the US, 80% in the UK, and 69.1% in the world had received at least one dose of a covid-19 vaccine) and a growing number of people have been reinfected. Our study suggests that the effectiveness of nirmatrelvir is maintained in people who are not vaccinated, in those who are vaccinated, or have received a booster dose, and in those with a primary infection or reinfection.…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Real world effectiveness studies from Israel, Hong Kong, and the UK provided evidence of the effectiveness of nirmatrelvir during the early days of the omicron surge when BA.1 or BA.2 was the predominant subvariant. [3][4][5] Most people infected in the omicron predominant era had been vaccinated (80% of people in the US, 80% in the UK, and 69.1% in the world had received at least one dose of a covid-19 vaccine) and a growing number of people have been reinfected. Our study suggests that the effectiveness of nirmatrelvir is maintained in people who are not vaccinated, in those who are vaccinated, or have received a booster dose, and in those with a primary infection or reinfection.…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…Real world evidence studies from Israel, Hong Kong, and the UK suggested that nirmatrelvir was associated with a reduced risk of admission to hospital or death during the early days of the omicron surge. [3][4][5] Omicron has since replaced previous variants, has spawned subvariants, many people recently infected have been vaccinated, and many people have been reinfected (ie, had a previous SARS-CoV-2 infection). [6][7][8] The effectiveness of nirmatrelvir in reducing the risk of admission to hospital or death by vaccination status and by previous history of SARS-CoV-2 infection is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Up to February 27, 2023, seven of the 14 studies were published in an international peer-reviewed journal, [26][27][28][29][30][31][32] and seven were published as pre-prints. [33][34][35][36][37][38][39] Three of the preprints have since been published in a peer-reviewed journal . [40][41][42] Studies reported on populations from the US (n=2), UK (n=6), Italy (n=1), Denmark (n=1), France (n=1), Japan (n=2), and Qatar (n=1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven studies were conducted via secondary analyses of healthcare data, with sources including OpenSAFELY, 38,39 Discover-NOW dataset, 36 SAIL Databank, 33 and the Hospital Episode Statistics database. 35 Other data sources included patient electronic medical records or charts, 27,28,32,37 insurance claims, 26 and laboratory data.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation